2022
DOI: 10.1007/s11096-022-01467-8
|View full text |Cite
|
Sign up to set email alerts
|

Designated prescribing practitioners: a theory-based cross-sectional study of stakeholders’ views on implementation of a novel pharmacy regulator mandated preceptorship model

Abstract: Background Scottish Government is increasing independent prescribers (IP) in community pharmacy (CP). A new preceptorship model using IPs as Designated Prescribing Practitioners (DPPs) has been introduced. Aim To investigate stakeholder views of implementation of a novel regulator mandated IP course preceptorship model. Method A theory-based online pre-piloted survey of stakeholders including e.g. directors of pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Also, the respondents did not have any concerns about the clinical and diagnostic skills of DPPs or their abilities to work collaboratively. The same survey also reported a very high level of agreement on the urgent need to implement the role of DPPs as supervisors, which advantages outweigh the disadvantages (Jebara et al, 2022).…”
Section: Mentorshipmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, the respondents did not have any concerns about the clinical and diagnostic skills of DPPs or their abilities to work collaboratively. The same survey also reported a very high level of agreement on the urgent need to implement the role of DPPs as supervisors, which advantages outweigh the disadvantages (Jebara et al, 2022).…”
Section: Mentorshipmentioning
confidence: 90%
“…Few studies in the literature have discussed this point, as it is a novel way of supervision and is still in a growth phase. A survey of stakeholder views on the implementation of the role DPPs in 2022 found that the majority of respondents agreed on the ability of DPPs to report or respond to trainee concerns (Jebara et al, 2022). The majority of stakeholders agreed on the confidence and competence of DPPs in training, supervising, and assessing independent prescribers.…”
Section: Mentorshipmentioning
confidence: 99%